Galileo : A Very Short Introduction - Drake, Stillman (Oxford Oxford University Press, 2001)
In a startling reinterpretation of Galileo's trial, Stillman Drake advances the hypothesis that Galileo's prosecution and condemnation by the Inquisition was caused not by his defiance of the Church but by the hostility of contemporary philosophers. Galileo's own beautifully lucid arguments are used in this volume to show how his scientific method was utterly divorced from the Aristotelian approach to physics; it was based on a search not for causes but for laws. Galileo's methods had an overwhelming significance for the development of modern physics, and they led to a final parting of the ways between science and philosophy. Now, in this extraordinary and concise introduction, Drake provides a stimulating view of Galileo's life and works, providing a fresh perspective on Galileo's methodology and his final incrimination.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Italy -- Astronomers -- Galilei, Galileo, 1564-1642